Dense mesopelagic sound scattering layer and vertical segregation of pelagic organisms at the Arctic-Atlantic gateway during the midnight sun - Priou, Pierre; Nikolopoulos, Anna; Flores, Hauke; Gradinger, Rolf; Kunisch, Eirin; Katlein, Christian; Castellani, Giulia; Linders, Torsten Theodor; Berge, Jørgen; Fisher, Jonathan A.D.; Geoffroy, Maxime (Progress in Oceanography, 2021)
Changes in vertical and spatial distributions of zooplankton and small pelagic fish impact the biological carbon pump and the distribution of larger piscivorous fish and marine mammal species. However, their distribution and abundance remain poorly documented at high latitudes because of the difficulties inherent to sampling relatively fast-moving organisms in ice-covered waters. This study documents the under-ice distribution of epipelagic and mesopelagic organisms at the Arctic-Atlantic gateway in spring, during the midnight sun period, using ice-tethered and ship-based echosounders. An epipelagic surface scattering layer composed of copepods consistently occupied the top 60 m and was associated with cold polar surface water (mean temperature of −1.5 °C). A mesopelagic deep scattering layer (DSL), partly composed of fish, persisted between 280 m and 600 m and was associated with modified Atlantic water. Backscattering strength within the DSL was higher than previously reported in the Arctic and north Atlantic, and increased by two orders of magnitude over the continental slope where one of the Atlantic water pathways enters the Arctic Ocean. Mesopelagic organisms did not perform diel vertical migrations. The consistent segregation between copepods at the surface and their predators at mesopelagic depths suggests limited predator–prey interactions during the midnight sun period, even under the ice cover. Predation on copepods by mesopelagic organisms, including fish, could thus be limited to very pulsed events during the seasonal vertical migration of copepods to and from overwintering depths. This suggests that the arctic mesopelagic food web may be decoupled from secondary production in the epipelagic layer throughout most of the year.